2016
DOI: 10.1038/srep38363
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Molecular Organization of Human Neuraminidase-1: Transmembrane Topology and Dimerization Ability

Abstract: Neuraminidase 1 (NEU1) is a lysosomal sialidase catalyzing the removal of terminal sialic acids from sialyloconjugates. A plasma membrane-bound NEU1 modulating a plethora of receptors by desialylation, has been consistently documented from the last ten years. Despite a growing interest of the scientific community to NEU1, its membrane organization is not understood and current structural and biochemical data cannot account for such membrane localization. By combining molecular biology and biochemical analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 61 publications
8
55
0
2
Order By: Relevance
“…One neuraminidase mediating platelet desialylation is neuraminidase-1 (NEU1), which resides in the platelet lysosome and is trafficked to the plasma membrane after refrigeration 5 . NEU1 is membrane-bound and can desialylate platelet glycoproteins including GPIbα 5, 24 . However, it was not clear how refrigeration induces movement of NEU1 from the lysosome to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…One neuraminidase mediating platelet desialylation is neuraminidase-1 (NEU1), which resides in the platelet lysosome and is trafficked to the plasma membrane after refrigeration 5 . NEU1 is membrane-bound and can desialylate platelet glycoproteins including GPIbα 5, 24 . However, it was not clear how refrigeration induces movement of NEU1 from the lysosome to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EDP induce an enhanced invasion of melanoma cells (46)(47)(48). Implication of EDP and Neu-1 in other cancer types has also been shown: Neu-1 is involved in the development of hepatocellular carcinoma (49) and ovarian cancer (50). Altogether, these data indicate that Neu-1 plays a key role in the development and the amplification of several cancers and can constitute a new target to slow down cancer progression.…”
Section: Neu-1 Tm Domain As a Potential Target In Cancersmentioning
confidence: 85%
“…How these enzymes are associated with the membrane remains controversial. For Neu1, some studies suggested a C-terminal transmembrane domain, whereas other studies excluded a transmembrane region proposing a lipid anchor 75,76 . Subcellular location and activity of sialidases might differ depending on the physiological conditions and the cell types, as demonstrated by the polysialic acid processing by Neu1 77 and the involvement of Neu4 in hippocampal memory processing 78 .…”
Section: Identified Sialidases and Sialyltransferases In Synaptosomesmentioning
confidence: 99%